Memory at stake – Swedish private archives in a changing landscape. Issue 3 (1st September 2016) - Hansen, Lars-Erik; Sundqvist, Anneli
Abstract: Private archival institutions collect records from churches, trade unions, companies, associations and any other non-government organisations. Organisations and associations have played an important role in Swedish public life during the twentieth century, being agents in the process of democratisation and societal change leading to the modern welfare state. Citizens' influence on politics and administration has to a large extent been channelled through organisations of various kinds. During the second half of the last century, a nationwide network of so-called popular movement archives emerged, initiated by the records creating organisations themselves. These institutions are important complements to the public archives, covering other spheres of society and contributing to preserve the history of everyday life, and political and social development. However, the traditional forms of stable rule-based organisations with structured records creation are dissolving, and being replaced with more loosely connected and continuously changing communities working in an online environment. Furthermore, the last decades have witnessed the emergence of digital information, and most private institutions lack the technological infrastructure and knowledge to receive digital records for long-term preservation. This study explores the developments and current status of popular movement archives in Sweden, and the challenges they are facing, in order to outline a scenario for future development and consequences for future societal memory.